The Institute for Preventative Sports Medicine (IPSM)
The Institute for Preventative Sports Medicine (IPSM) is a non-profit research organization dedicated to the prevention of sports-related injuries and health care cost containment. Its research focuses on finding effective and practical ways to reduce sports related injuries and speed the rehabilitation of injured athletes. The Institute also seeks ways to disseminate its research findings to benefit the public at large.